2013
DOI: 10.1016/j.ijmedinf.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a clinical decision rule-based alert system for drug dose adjustment in patients with renal failure intended to improve pharmacists’ analysis of medication orders in hospitals

Abstract: This study strongly suggests that an alert system would be complementary to the pharmacists' activity and contribute to drug prescription safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…There is another potential issue with prescriber-based CDSS. It has been reported that EHR alerts displayed during CPOE are commonly ignored [9,[25][26][27]. While prescribers may be more likely to act on the severity of the alert [25], it is unknown how prescribers view the severity of renal dose adjustment alerts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is another potential issue with prescriber-based CDSS. It has been reported that EHR alerts displayed during CPOE are commonly ignored [9,[25][26][27]. While prescribers may be more likely to act on the severity of the alert [25], it is unknown how prescribers view the severity of renal dose adjustment alerts.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical decision support systems (CDSS) have been developed within electronic health records (EHR) to identify patients with renal impairment when such patients are prescribed a medication that requires renal adjustment/contraindication [4,[8][9][10]. These systems require patient-specific laboratory and demographic data to be available during medication ordering or dispensing.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Computerized physician order entry (CPOE) systems currently include DDI checking tools, most of which are integrating alert systems [209]. In some advanced systems, renal and hepatic functions can also be incorporated, and dose adaptation might be recommended according to the estimated GFR and/or liver functional status [210]. A recent meta-analysis highlighted the discrepancy between the high prevalence of potential DDIs and the low prevalence of actual DDIs leading to clinical harm [211].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Boussadi and colleagues 43 investigated alert systems embedded within electronic health records (EHRs), such as those that addressed renal function and anticoagulation concerns, to complement pharmacist activities and improve safety benefits. Of the 5006 drug prescription lines analyzed, the alert system correctly analyzed 4863 (97.14%), whereas the pharmacists correctly analyzed 4745 (94.77%) of the same lines.…”
mentioning
confidence: 99%